Implementasi Hak Imunitas Advokat Dalam Melakukan Pembelaan terhadap Klien - Dinda Nurul Khotimah; Fauziah Lubis; Tiara Nabila (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Legal disputes are a constant in everyday people's lives. The legal dispute in question cannot be satisfied by using deliberation for consensus, so it must be satisfied by using legal channels. To assist in the resolution of such legal disputes, which must be confirmed by a court of law, professional legal advice is required. Professional advice in question can be obtained from legal advice given by a lawyer. Advocates as the only legal practitioners in Indonesia have the professional integrity needed to carry out their work. In particular, Article 16 of Law no. 18 of 2003 concerning Advocates states that advocates may not be contacted either privately or openly when launching their capacity to get clients. When the lawyers in question are giving legal advice, especially when they are negotiating with other parties, problems suddenly arise. Based on the results of research that the implementation of the advocate's immunity rights has not been fully implemented in accordance with the provisions in Article 16 of Law Number 18 of 2003 concerning Advocates. This can be seen from the majority of the opinions of law enforcement respondents in the City of Magelang and its surroundings. The factors that impede the implementation of advocate immunity rights are divided into l2 l(two), lnamely linternal lfactors l(advocate lbehavior lthat ldoes lnot lrespect lthe lcode lof lethics lof lthe ladvocate lprofession land ladvocate lorganizations lthat lare ldivided) land lexternal lfactors l(other llaw lenforcers l(investigators, lprosecutors, ljudges) l) land lthe lpublic l(opposing lparties lor lthe lvictim's lfamily) lwho ldo lnot lknow lor ldo lnot lunderstand land/or lunderstand lthe lexistence lof ladvocate limmunity lrights]. lThe lsolution lto lthis lproblem lis lto lform la lsingle lbar lfor ladvocate lorganizations l(single lbar) lthat lcan lmonitor ladvocate lbehavior land lcan ldefend ladvocate lrights lthat lhave lbeen lviolated land lestablish lproportional lcooperative lrelationships l(according lto ltheir lrespective lduties, lfunctions land lauthorities) lwith lother llaw lenforcers. l(investigators, lprosecutors, ljudges) lin lupholding lthe ljustice lsystem lin lIndonesia.